Belonging and 'Unbelonging': Jewish refugee and survivor women in 1950s Britain. Issue 1 (2nd January 2017) - Davis, Angela
ABSTRACT: This article analyses the life stories of female Jewish refugees and survivors in 1950s Britain in order to explore their relationship with the existing Jewish community and wider society. The paper is based on an analysis of twenty-one oral history testimonies from the Jewish survivors of the Holocaust collection held at the British library. Around 50, 000 Jewish refugees from Central Europe came to Britain in the 1930s after fleeing from Hitler. In addition, a relatively small number of camp survivors and former hidden children settled in the country after the war; the Board of Deputies of British Jews Demographic Unit estimates the figure at 2000. This article considers how these refugee and survivor women tried to find a place for themselves within 1950s Britain. Looking at their experiences of arrival, work and home, it reflects upon the discrimination and hostility they faced, and they ways they tried to deal with this. Finally it discusses what this meant for their sense of belonging or 'unbelonging'.